Budaya Politik Masyarakat Kampung Adat Urug Kecamatan Sukajaya Kabupaten Bogor pada Pemilihan Bupati Bogor Tahun 2018 - Muhamad Nurul Firdaus (Jurnal Ilmu Sosial dan Humaniora, 2026)
The Regional Head Election (Pilkada) represents a concrete manifestation of democratic practice at the local level. However, within indigenous communities, political participation is not solely shaped by formal democratic mechanisms but is also strongly influenced by cultural values passed down through generations. Kampung Adat Urug, located in Sukajaya District, Bogor Regency, is an indigenous community that continues to strongly preserve its social system and customary norms. This condition gives rise to political practices with distinctive characteristics compared to those of modern societies in general. This study aims to analyze the political culture of the Kampung Adat Urug community in the 2018 Bogor Regent Election, focusing on political orientation, patterns of participation, and the role of customary leaders in the local political process. The research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with customary leaders and cultural practitioners, as well as documentation studies of relevant sources. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The analytical framework for political culture refers to the theory of Gabriel A. Almond and Sidney Verba. The findings indicate that the political culture of the Kampung Adat Urug community is characterized by a parochial–subject orientation with a tendency toward traditional participatory practices. Customary values such as deliberation, mutual cooperation, and respect for customary leaders are dominant factors shaping the community’s political orientation and behavior. Political participation remains active but is framed by customary principles that emphasize social harmony and reject transactional political practices. The political culture of the Kampung Adat Urug community reflects a synthesis between the modern democratic system and enduring local values that are preserved and upheld.